Vanillin: The Case for Greener Production Driven by Sustainability Megatrend. Issue 6 (2nd May 2019) - Ciriminna, Rosaria; Fidalgo, Alexandra; Meneguzzo, Francesco; Parrino, Francesco; Ilharco, Laura M.; Pagliaro, Mario
Abstract: Approaching the end of the second decade of the 21 st century, almost the whole demand of vanillin is met by the synthetic product obtained either via a petrochemical process starting from phenol and glyoxylic acid or from energy intensive alkaline oxidative depolymerization of lignin. Only a minor fraction is comprised of natural vanillin obtained from ferulic acid fermentation, and even less of highly valued Vanilla planifolia extracts. Are there alternative green production methods? And, if yes, are they suitable to find practical application? Abstract : Vanilla green ! Only a minor fraction of commercial vanillin is comprised of natural vanillin obtained from ferulic acid fermentation, and even less of highly valued Vanilla planifolia extracts. Are there alternative green production methods? And, if yes, are they suitable to find practical application?